Hidden - Piutau, Mau'lote (Te Kaharoa, 2020)
Soft luscious lips, honey soft brown eyes, a beautiful lavender aroma that you can smell even from a mile away; her soft alluring curls bouncing off her shoulders as she strides to the front of the church. Am tempted to walk to the front to kiss her, claiming her as mine, but I know better than to do that. My heart beats rapidly as I watch her laugh. Her laughter is a sweet melody to my ears; a beautiful song I could never get enough off like a hymn I need in my life. I remove my gaze from her as I try to pull myself together before I do something that I will regret. How can those boys make her laugh like that when I couldn’t even make her smile at me?